Perspective annotation for numerical representations - Hofman, Jake; Dudík, Miro; Goldstein, Daniel G. (United States Patent Application, 2018)
Various techniques for providing perspective annotation to numerical representations are disclosed herein. For example, a method includes detecting a numerical representation in an original content and retrieving one or more perspectives from a database based on the detected numerical representation. The one or more perspectives individually include a restatement of information contained in the numerical representation. The method can also include annotating the original content with the retrieved one or more perspectives to form an annotated content.